2017
DOI: 10.1016/j.jid.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Versus 5% Imiquimod for Nodular and Superficial Basal Cell Carcinoma: 5-Year Results of the SINS Randomized Controlled Trial

Abstract: Abbreviations BCC = basal cell carcinoma; nBCC = nodular basal cell carcinoma sBCC = superficial basal cell carcinoma; PDT = photodynamic therapy RCT = randomised controlled trial Abstract -200 words Main text -2600 words Tables -1 Figures -1 References -23 2 ABSTRACT Background: We previously reported modest clinical 3-year benefit for topical imiquimod compared with surgery for superficial or nodular basal cell carcinoma (sBCC, nBCC) at low risk sites in our non-inferiority randomised controlled SINS tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 22 publications
1
109
0
8
Order By: Relevance
“…Basal cell carcinoma (BCC), the most common nonmelanoma skin cancer among the white population, is an important health problem worldwide and has a rapidly increasing incidence (Flohil et al, 2013;Lomas et al, 2012) As a result, BCC causes high medical consumption and health care costs (Housman et al, 2003). Although surgical excision is the gold standard for treatment of BCCs, different studies suggest that noninvasive therapies are useful alternatives to surgery for treatment of superficial BCC (sBCC) (Szeimies et al, 2008;Williams et al, 2017). Besides being less invasive, topical therapies also have other advantages like good cosmetic outcome, according to evaluation by physicians (Bath-Hextall et al, 2014;Cosgarea et al, 2013;Szeimies et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal cell carcinoma (BCC), the most common nonmelanoma skin cancer among the white population, is an important health problem worldwide and has a rapidly increasing incidence (Flohil et al, 2013;Lomas et al, 2012) As a result, BCC causes high medical consumption and health care costs (Housman et al, 2003). Although surgical excision is the gold standard for treatment of BCCs, different studies suggest that noninvasive therapies are useful alternatives to surgery for treatment of superficial BCC (sBCC) (Szeimies et al, 2008;Williams et al, 2017). Besides being less invasive, topical therapies also have other advantages like good cosmetic outcome, according to evaluation by physicians (Bath-Hextall et al, 2014;Cosgarea et al, 2013;Szeimies et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies on long-term effectiveness of noninvasive treatment of sBCC have been published. Head-to-head studies are pivotal to reach consensus in international BCC guidelines on the first choice noninvasive treatment to compare effectiveness (Roozeboom et al, 2012;Williams et al, 2017). We previously showed that the efficacy of 5% imiquimod cream is superior and 5-fluorouracil cream not inferior to methyl aminolevulinate photodynamic therapy (MAL-PDT) in the treatment of sBCC at 3-year follow-up (Roozeboom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1. 11,[35][36][37][38][39][40][41][42][43][44][45][46][47] All 14 studies were written in the English language. The articles were published from 1986 to 2018.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…There were similar cosmetic outcomes. 31 The main side-effects of the treatment are erythema, crusting, pain, flu-like symptoms and ulceration, which can be severe. Topical imiquimod is not recommended for high-risk BCC or SCC as recurrence rates are too high.…”
Section: The Patient Is Notmentioning
confidence: 99%